Breaking Barriers: Exploring Language and Pedagogical Challenges in Teaching the Filipino Subject - Yna Jane H. Seballos; Rochelle C. Ramos; Justine A. Canto; Ruel T. Bonganciso (Humanities, Society, and Community, 2024)
The Philippine educational system has faced several challenges, including a teacher shortage that created pedagogical difficulties across many subjects. This study identified the language and pedagogical challenges that English teachers encounter when teaching the Filipino subject. The researchers used the transcendental phenomenology method to collect data through one-on-one interviews with English teachers. The data explicitation was done by using the modified Van Kaam Analysis to characterize the challenges English teachers face by examining the respondents and then comparing and contrasting their responses by following the seven (7) steps: listing and grouping, reduction and elimination, clustering and thematizing, validation, individual textual description, individual structural description, and textural-structural description. This study revealed that the challenges faced by English teachers in teaching the Filipino subject were as follows: (1) the misplacement of English teachers because of a shortage of teachers; (2) the need for out-of-field pedagogical adjustment; and (3) rapid language transition. Moreover, presenting interventions like using various strategies and approaches to address these challenges.